Study guides

☆☆

More answers

13 + c = -9

subtract 13 from both sides

c = -9 - 13

c = -22

Q: 13 plus c equals -9

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

13

6 + 12 - 5 = 13

the answer is a

4c+2 = 3c+9 4c-3c = 9-2 c = 7

A.

Related questions

If 9 - 2c + 3 = -13, then c would be 12.5

13+c = -39 c = -39-13 c = -52

13

-4 + c = -9 -4 + 4 + c = -9 +4 c = -9 + 4 c = -5

6 + 12 - 5 = 13

a=5: c=4

the answer is a

2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4

This is the associative law for addition: If a, b, c are any numbers then: a + (b + c) = (a + b) + c

144 Formula: c= (a2)+(ab)

yes

4c+2 = 3c+9 4c-3c = 9-2 c = 7

People also asked

Featured Questions